2019
DOI: 10.1159/000503894
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Nodosum: A Manifestation of Salmonella Infection

Abstract: Erythema nodosum is a delayed-type hypersensitivity reaction with an unknown trigger in the majority of cases. It is characterized by the development of erythematous tender nodules on the shins. Septal panniculitis without vasculitis is a characteristic histopathological finding. We report the case of a 26-year-old woman who presented with a four-day history of an erythematous swollen left lower limb. She was treated with intravenous clindamycin for suspected cellulitis. However, her symptoms persisted. Punch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It is characterized by the sudden development of painful erythematous nodules and plaques on the extensor surfaces of the lower limbs. Recurrences are rare, and the lesions typically resolve on their own without scarring, necrosis, or atrophy [7,8]. The typical presentation of erythema nodosum includes the abrupt appearance of nodules and raised plaques on the lower legs.…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by the sudden development of painful erythematous nodules and plaques on the extensor surfaces of the lower limbs. Recurrences are rare, and the lesions typically resolve on their own without scarring, necrosis, or atrophy [7,8]. The typical presentation of erythema nodosum includes the abrupt appearance of nodules and raised plaques on the lower legs.…”
Section: Resultsmentioning
confidence: 99%
“…A study among children from Israel reported streptococcal infections followed by EBV infections (4) . The first case of EN coexisting with salmonellosis was published by Grossman and Katz in 1984 (10) . Only few case reports of ED in patients diagnosed with Salmonella infection can be found in English-language literature (9)(10)(11)(12)(13) .…”
Section: Discussionmentioning
confidence: 99%
“…The first case of EN coexisting with salmonellosis was published by Grossman and Katz in 1984 (10) . Only few case reports of ED in patients diagnosed with Salmonella infection can be found in English-language literature (9)(10)(11)(12)(13) . S. Typhimurium and S. Typhi (13) are the most common causes of EN, whereas S. Enteritidis is less commonly reported (10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Most cases of EN present as acute eruptions of tender erythematous or bruise-like nodules located bilaterally on the anterior and lateral surfaces of the lower legs. 4 EN is sometimes misdiagnosed as cellulitis, especially when the nodules are not evident 5 or the lesion is not bilateral. Although MRI of the right lower leg was performed for diagnosis, the findings were consistent with nonspecific inflammation of the subcutaneous fat.…”
mentioning
confidence: 99%